The Healing - Santos, Vilma; Chiu, Kim; Tarog, Jerrold; Santos-Concio, Charo; Santos, Malou (2012)
Seth (Vilma Santos) witnesses a miracle when her paralyzed father is healed by Elsa, a faith healer. Her neighbors, who suffer from different kinds of diseases, plead with her to bring them to Elsa. Cookie (Kim Chiu), the daughter of her husband asks to be healed as well. Seth agrees to help all of them. Right after they are healed, strange things happen...eventually leading to death. Feeling responsible for this turn of events, Set desperately seeks ways to end the curse. Will she find a way to stop the curse before it takes another life?